Ноотропы в комплексной терапии хронической ишемии мозга - Чекман, И. С.; Беленичев, И. Ф.; Демченко, А. В.; Боброва, В. И.; Горчакова, Н. А.; Кучеренко, Л. И.; Бухтиярова, Н. В.; Чекман, І. С.; Бєленічев, Ігор Федорович; Демченко, Аліна Вікторівна; Боброва, В. І.; Горчакова, Н. О.; et al. (My University, 2014)
Викладено клініко-фармакологічну характеристику ноотропов — однієї з найбільш продуктивних груп нейропсихотропних лікарських препаратів. Побудовано класифікацію ноотропних засобів за основним механізмом дії. Наведено приклади клінічного застосування препаратів при хронічній ішемії мозку. Clinical and pharmacological characteristics of nootropics — one of the most productive groups of neuropsychotropic drugs, are considered. Classification of nootropics based on the main mechanism of action is constructed. The examples of clinical use of drugs in patients with chronic cerebral ischemia are presented.
Nootropics in a comlex therapy of chronic cerebral ischemia
Keywords: цереброваскулярні захворювання; когнітивні порушення; нейропротекція; ноотропи; cerebrovascular diseases; cognitive disorders; neuroprotection; nootropics